2019
DOI: 10.1186/s13018-019-1372-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of subscapularis peel and lesser tuberosity osteotomy for double-row subscapularis repair technique in a cadaveric arthroplasty model

Abstract: IntroductionManagement of the subscapularis during shoulder arthroplasty is controversial. The purpose of this study was to compare the biomechanical performance of subscapularis peel (SP) and lesser tuberosity osteotomy (LTO) in a cadaveric model.MethodsThe subscapularis and proximal humerus were dissected from all soft tissues in 21 fresh-frozen human cadaveric shoulders and randomized to undergo SP, LTO, or standard subscapularis tenotomy (ST, control). For SP and LTO, six #5 sutures were passed through eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Effective subscapularis repair 71 during surgery is therefore mandatory; a review of biomechanical cadaveric studies suggests superior load to failure for the osteotomy at time zero but no difference at cyclic loading. 72 , 73 While de Wilde suggested that a C-block lesser tuberosity osteotomy might prevent postoperative subscapularis fatty infiltration, a recent systematic review reported no statistical difference in clinical and radiological outcomes between tenotomy, peel and osteotomy. 74 76 In case of postoperative rupture, a prompt secondary repair can be considered to prevent instability but has been associated with variable results.…”
Section: Anatomic Total Shoulder Arthroplasty (Atsa)mentioning
confidence: 99%
“…Effective subscapularis repair 71 during surgery is therefore mandatory; a review of biomechanical cadaveric studies suggests superior load to failure for the osteotomy at time zero but no difference at cyclic loading. 72 , 73 While de Wilde suggested that a C-block lesser tuberosity osteotomy might prevent postoperative subscapularis fatty infiltration, a recent systematic review reported no statistical difference in clinical and radiological outcomes between tenotomy, peel and osteotomy. 74 76 In case of postoperative rupture, a prompt secondary repair can be considered to prevent instability but has been associated with variable results.…”
Section: Anatomic Total Shoulder Arthroplasty (Atsa)mentioning
confidence: 99%
“…While the limitations of ST have caused a shift toward LTO and SP for subscapularis management, many studies have reported no difference between LTO and SP repairs. 5,7,10 In a biomechanical study comparing LTO and SP, Buraimoh et al found no differences in repair gapping, fatigue failure, or load to fatigue. 13 In their randomized controlled trial evaluating a cohort of 43 patients with LTO or SP, Lapner et al found no differences between the two techniques with regard to postoperative strength or patient-reported outcome scores.…”
Section: Discussionmentioning
confidence: 99%
“…Subscapularis management remains an area of active debate with several different techniques currently employed, including a subscapularis tenotomy (ST), subscapularis peel (SP), or a lesser tuberosity osteotomy (LTO). [4][5][6][7] ST has been the traditional approach to the TSA, as it provides easy access to the glenohumeral joint while leaving a tendon stump for direct tendon to tendon repair. However, many complications have been reported regarding the lack of subscapularis function after TSA, and in some cases, it is difficult to complete an adequate repair.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations